The influence of brand image and brand personality on brand loyalty - Mabkhot, Hashed Ahmed; Md. Salleh, Salniza; Shaari, Hasnizam (AENSInet Publications, 2015)
Several studies in the field of branding management, customer behavior have mentioned that there are variables related to affect customer brand loyalty such as perceived quality, brand awareness, brand equity, among others.However, few studies have attempted to consider the influence of brand image and brand personality. Even if any, they have reported conflicting findings. This paper proposes to examine the relationship between brand image and brand personality on brand loyalty.